Government’s Efforts To Minimize The Threat of Coastline Changes on the North Coast of Bengkalis Island - Siti Sarah; Tomi Aris; Surya Wiranto; Purwanto Purwanto (LPPM Universitas Trunojoyo Madura, 2022)
This study aims to analyse the changes in the coastline that will occur using geographic information system technology and formulate anticipatory efforts from the government to overcome the threat of abrasion on the north coast of Bengkalis Island, Riau Province. Bengkalis is a Regency located on the north coast of Riau Province, where the coastal area is very vulnerable to maritime disasters. This is evidenced by tidal waves or high tides that regularly occur at the end of the year in the north coastal area of the Bengkalis Regency. There are hundreds of houses and shopping centre shops submerged by the tide; this is causes harm to the community. In addition, the threat of abrasion, which causes changes to the coastline toward settlements, continues to increase every year; this problem threatens the country’s sovereignty because the worst possibility is to eliminate the island. This study found that coastal abrasion that occurred on the coast of Bengkalis Island reached 39 meters a year, and the average rate of change of the coastline was 14 meters a year.Without serious handling and countermeasures from the government, this will become a big problem.